PENERAPAN "GREEN TECHNOLOGY" BERBASIS TEKNOLOGI HIBRIDA PENGUPAS DAN PEMIPIL JAGUNG BERENERGI SURYA UNTUK MENINGKATKAN PRODUKTIVITAS DAN DAYA SAING - Ropiudin; Kavadya Syska (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The focus of this community service activity is to provide solutions to the problem of handling corn harvest/postharvest and corn farming in the Ngudi Rahayu I Farmer Group, Mentasan Village, Kawunganten District, Cilacap Regency, Central Java. The objectives of this activity are (1) to increase a group of people (corn farmer groups) who are economically independent, (2) to increase knowledge, skills, product quality, and the amount of turnover in corn farmer groups. The activity stages include: (1) the preparation stage, (2) the review stage, (3) the technology planning stage, (4) the technology transfer action plan stage, (5) the implementation stage, and (6) the evaluation stage. The results of community service are the application of solar-energy corn peeler and sheller hybrid technology and skills in farming management. Increasing knowledge and skills in applying technology in this activity was carried out to the Ngudi Rahayu I Farmer Group, Cilacap Regency, Central Java. This activity contributes to increasing the productivity and competitiveness of corn farmers. Increased productivity and competitiveness in the form of economic independence, increased knowledge, skills, product quality, and total turnover in corn farmer groups.